Comparison of passive and scanning irradiation methods for carbon-ion radiotherapy for breast cancer. (11th July 2018) - Matsubara, Hiroaki; Karasawa, Kumiko; Furuichi, Wataru; Wakaisami, Mitsuji; Shiba, Shintaro; Wakatsuki, Masaru; Omatsu, Tokuhiko; Inaniwa, Taku; Fukuda, Shigekazu; Kamada, Tadashi
Abstract: The dose distribution of passive and scanning irradiation for carbon-ion radiotherapy for breast cancer was compared in order to determine the preferred treatment method. Eleven Japanese patients who received carbon-ion radiotherapy for breast cancer were retrospectively analyzed. The original clinical plans were used for the passive irradiation method, while the plans for the scanning irradiation method were more recently made. Statistical analysis suggested that there was no significant difference in superiority in terms of dose distribution between the passive and scanning irradiation methods. The present study found that the scanning irradiation method was not always superior to the passive method, despite a previous study having reported the superiority of scanning irradiation. The present result is considered to arise from characteristics of breast cancer treatment, such as the simplicity of the organ at risk and the shallow depth point of the target from the skin. It is noteworthy that the present study suggests that the passive irradiation method can provide better dose distribution, depending on the case.